Za kamennoi stenoi. Budni nachal'nika detskoi kolonii. . Za kamennoi stenoi. Budni nachal'nika detskoi kolonii. . Behind the Stone Wall. Weekdays of the Head of a Juvenile Colony . За каменной стеной. Будни начальника детской колонии - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The documentary tells the story of a juvenile labor colony and its overseer. Contributors: Sadkovoi, Aleksandr (Director) Фильм о несовершеннолетних воспитанниках воспитательно-трудовой колонии и ее начальнике. Создатели: Садковой, Александр (Режиссер)